1986
DOI: 10.1002/clc.4960090103
|View full text |Cite
|
Sign up to set email alerts
|

Difference in the response to isoproterenol between asymmetric septal hypertrophy and symmetric hypertrophy in patients with hypertrophic cardiomyopathy

Abstract: Summary:The response to isoproterenol was studied in 9 patients with hypertrophic cardiomyopathy (HCM) and asymmetric septal hypertrophy (ASH), 9 patients with HCM and symmetric hypertrophy (SH), and 9 normal controls (NC), using digitized M-mode echocardiography. There was no significant difference in fractional shortening (FS) between ASH and SH, nor between SH and NC before isoproterenol infusion. During isoproterenol infusion, however, FS was significantly greater in ASH (60f6%) than in SH (53f7%) and NC (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…None of the patients with a significant gradient (>50 mm Hg) had a LVETI value <423 ms, and only 1 of the patients without a significant gradient had a LVETI >423 ms. The parallel increase of pressure gradient and LVETI in the patients in whom isoproterenol was infused sug gested that LVET is a reliable index which can identify patients with a gradient at rest and during pharmacolog ical intervention [28,35,36], A comparison of the current study with previous observations reveals considerable discrepancies. Stefadouros et al [37] found a correlation between pressure gradient and LVET in patients with hypertrophic cardio myopathy, but they found a better correlation with the PEP/LVET ratio.…”
Section: Control Groupcontrasting
confidence: 50%
“…None of the patients with a significant gradient (>50 mm Hg) had a LVETI value <423 ms, and only 1 of the patients without a significant gradient had a LVETI >423 ms. The parallel increase of pressure gradient and LVETI in the patients in whom isoproterenol was infused sug gested that LVET is a reliable index which can identify patients with a gradient at rest and during pharmacolog ical intervention [28,35,36], A comparison of the current study with previous observations reveals considerable discrepancies. Stefadouros et al [37] found a correlation between pressure gradient and LVET in patients with hypertrophic cardio myopathy, but they found a better correlation with the PEP/LVET ratio.…”
Section: Control Groupcontrasting
confidence: 50%
“…FS and pVs were larger in patients with HCM than in NC at rest and during exercise in the present study. Several studies reported hypercontractile condition of HCM (Bonow er af., 1981;Braunwald et al, 1964;Iida et al, 1986;Williams et al, 1973). In view of systolic performance, exercise capacity and cardiac reserve to exercise can be thought to be excellent in patients with HCM, as shown in our previous paper (Sugishita er al., 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been described previously (Iida et al, 1983(Iida et al, , 1986Matsuda et al, 1983). From the digitized data, the following values were calculated and printed out: (1) the left ventricular enddiastolic dimension (EDD) which was determined at the time of the R wave of the electmcardiogram and the end-systolic dimension (ESD) which was determined at the time of onset of the second heart sound on the phonocardiogram.…”
Section: Digitized Echocardiographic Analysismentioning
confidence: 99%
“…ISP Echocardiography The ISP test was performed in the afternoon in all 22 patients using a previously described technique. [11][12][13][14][15] Briefly, the patient lay in the supine position in a darkened room, and ISP was infused for 5 min through an antecubital vein at doses of 0.01 and 0.02 g‱kg -1 ‱min -1 using a calibrated infusion pump. During ISP infusion, the electrocardiogram was monitored continuously.…”
Section: Echocardiographic Studiesmentioning
confidence: 99%